Direct measurement of the Higgs self-coupling in e+e− → ZH - Shivaji, A. (Elsevier, 2019)
A new method to measure the trilinear Higgs self-coupling λ3in a single Higgs production process is proposed. Time-reversal-odd (T-odd) asymmetries in the process e+e−→ZH, Z→f ̄fare computed from the absorptive part of the electroweak one-loop amplitude. Since the T-odd asymmetries measure the tree-level t-channel ZH→ZHscattering, they can be direct probes of λ3. The proposed method is quite challenging; a relatively large statistics and polarized e+e−beams are demanded. However, this is probably the only approach to directly measure λ3in e+e−collisions, when a beam energy above the ZHHproduction threshold is not availabl
Only IISERM authors are available in the record.
Keywords: Trilinear Higgs; Asymmetries; λ3in e+e−collisions